The effect of contact time on the potency of the crude toxin from lagocephalus lunaris lunaris when interacted with kappa carrageenan gel. - Noriega, Ellen G. (2001.)
Toxicity reduction as contact time increase and was found to be significant using the ANOVA for One-Way Classification. The mean values of the toxicity at different contact times were also subjected to Duncan's Multiple Range Test and it was found out that the average toxicity between 0-minute and 10-minute contact times as well as between 10 and 20-minute contact times are not significantly different while the average toxicity at 0 contact time compared with at 30-minute contact time interaction is significantly larger as well as the 10-minute compared with that at 30-minute and also the 20-minute compared with that at 30-minute contact time interaction. The study determined the concentration of the toxin using Sakaguchi Test and toxicity level of the crude toxin extracted from the ovary of Lagocephalus lunaris lunaris. Puffer fish samples were taken from Brgy. Nipa, Banate. The crude toxin with known toxicity was made to interact with the kappa carrageenan gel at different contact times. Using spectrophotometric analysis, results showed that the sample contains TTX expressed as mg arginine per kg sample which is 264.66 and its toxicity is 0.31 MU/g using the mouse bioassay method. Results in the interaction showed an increase in percent
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Lagocephalus lunaris lunaris -- Kappa Carrageenan Gel; Crude Toxin